Manual de Procedimientos para el Programa INTEGRATEC del Departamento DEVESA del Tecnológico de Costa Rica, Campus Tecnológico Local San Carlos - Araya-Sánchez, Yendry María (Instituto Tecnológico de Costa Rica, 2008)
The main objective of this project is to prepare a Manual of Procedures that will facilitate the operation of the student integration program, IntegraTEC, of the DEVESA Department of the Technological Institute of Costa Rica, at the San Carlos Regional. In addition, it´s proposed to analyze the procedures that are currently carried out in the program, by means of the removal of all the aspects that are part of the procedures, making an adequate documentation of each one, to make an implementation proposal. In order to collect the information of the procedures and thus meet the objectives proposed in the document, the use of a questionnaire was used to analyze processes, unstructured interviews were conducted with the different people in charge of developing the procedures and He gave the observation of them, for their uprising. In addition, the matrix method is used for feedback for the analysis of each documented procedure. The procedures of the IntegraTEC SC program of DEVESA of the Tecnológico de Costa Rica were documented, due to the lack of a Procedures Manual that allows the team members to identify the procedures and perform them in a standardized manner each year, this with so that the development of this program at headquarters performing efficiently and effectively.
Práctica Profesional (Bachiller en Administración de Empresas). Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Procedimientos; Políticas; Diagramas de flujo; Estudiantes; Líderes; Vida en comunidad; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies